A family secret - Heuvel, Eric, 1960- (Farrar Straus Giroux, 2009)
While searching his Dutch grandmother's attic for yard sale items, Jeroen finds a scrapbook which leads Gran to tell of her experiences as a girl living in Amsterdam during the Holocaust, when her father was a Nazi sympathizer and Esther, her Jewish best friend, disappeared.